On the first‐order and buckling behaviour of thin walled regular polygonal tubes. Issue 4 (November 2016) - Gonçalves, Rodrigo; Camotim, Dinar
Abstract: This paper summarizes the work carried out in the context of an ongoing investigation that aims to understand and characterize the structural behaviour of thin‐walled single‐cell regular convex polygonal section (RCPS) tubes, such as those widely employed in the steel construction industry. In particular, the first‐order and buckling (bifurcation) behaviours are addressed and it is shown that they exhibit several peculiarities, stemming essentially from the cross‐section rotational symmetry, and can be significantly influenced by distortion‐type deformation. The analytical and numerical results reported in this paper are obtained using generalized beam theory (GBT) and its computationally efficient specialization for RCPS recently developed by the authors [1]. In particular, the unique modal decomposition features of GBT make it possible to i) identify the most relevant cross‐section deformation modes, ii) draw valuable conclusions concerning the mechanics of the problem under consideration from the analysis of the (modal) solution, and iii) develop analytical and semi‐analytical formulae for problems of significant practical interest.